Wireless Charging Technology Improvement for New Energy Vehicles - Su, Ruilin (International Journal of Mechanical and Electrical Engineering, 2024)
In the operation of new energy vehicles, the energy supply method is directly related to the range and stability of the vehicle, and wireless charging technology is becoming a hot spot in the industry because of its efficient and convenient characteristics. This paper will discuss the core technology of wireless charging in new energy vehicles, covering the related equipment construction, compensation network design, and the design of key components of wireless charging technology improvement in new energy vehicles. The article will analyse the detailed results of the actual operation of the system, aiming to provide theoretical support and practical guidance for the application of wireless charging technology in new energy vehicles, and at the same time promote the further development of the new energy vehicle industry.